Kontribusi perilaku game online terhadap motivasi belajar siswa SMA - Denis Wengku Triatmojo (Fakultas Psikologi, 2019)
The online gaming behaviour referred to in this study is an individual response or reaction to the stimulation of online games or games connected via the Internet network. One factor that can influence the motivation to learn is the external factor or environmental factors that are parents, with the social support of parents then students should students have a high motivation to learn. The purpose of this research is to know the contributions of the behavior of online gaming to the learning motivation of high school students. This research is quantitative research with correlational design. The subject of this research was Shalahuddin high school student 94 students. The techniques used in sampling are total sampling techniques or saturated samples. The measuring instrument used in this study uses two scales of the scale of online gaming behaviour and learning motivation. The results showed that there was a link between the behavior of online gaming with the motivation of learning students (P = 0.000 > 0.05, r =-0.432) that is, there is a negative relationship between online gaming behaviour and the students ' learning motivation so that more students Spend time playing games online then the motivation of learning is getting lower.